Antifungal activity of silver nanoparticles in combination with ketoconazole against Malassezia furfur - Javier Esteban Mussin; María Virginia Roldán; Florencia Rojas; María de los Ángeles Sosa; Nora Pellegri; Gustavo Giusiano (AMB Express, 2019)
Abstract Malassezia furfur is lipophilic and lipid-dependent yeast, inhabitant of human skin microbiota associated with several dermal disorders. In recent years, along with the advances in nanotechnology and the incentive to find new antimicrobial drugs, there has been a growing interest in the utilization of nanoparticles for the treatment of skin microbial infections. This work aimed to study the in vitro inhibitory activity of silver nanoparticles (AgNP) against 41 M. furfur clinical isolates, visualize the interaction between AgNP-Malassezia, evaluate the synergism with ketoconazole (KTZ) and to produce an antimicrobial gel of AgNP–KTZ. The synthesized AgNP were randomly distributed around the yeast surface and showed a fungicidal action with low minimal inhibitory concentration values. AgNP showed no antagonistic effect with KTZ. The broad-spectrum antimicrobial property with fungicidal action of AgNP and its accumulation in affected areas with a sustained release profile, added to the great antifungal activity of KTZ against Malassezia infections and other superficial mycoses, allowed us to obtain a gel based on carbopol formulated with AgNP–KTZ with the potential to improve the topical therapy of superficial malasseziosis, reduce the number of applications and, also, prevent the recurrence.